2009
DOI: 10.1891/0886-6708.24.6.786
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Symptoms as a Mediating Factor on the Effects of Exposure to Community Violence Among Children in Cape Town, South Africa

Abstract: Research conducted over the past 20 years has linked exposure to violence to posttraumatic stress disorder (PTSD) in children both in the United States and South Africa, but very little research has investigated PTSD as a mediating variable between exposure to violence and other problems. The purpose of the current research was to determine if PTSD acts as a mediating variable between exposure to violence and depression, and exposure to violence and aggressive and violent behavior at school among a sample of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…PTSD rates in adolescents from the low-income areas of South Africa have been found to be between 20 and 25% (Seedat, Nyamai, Njenga, Vythilingum, & Stein, 2004 ; Suliman et al, 2009 ), which is at least three times the rates of European and North American adolescents (Kessler, Sonnega, Bromet, Hughes, & Nelson, 2005; Perkonigg, Kessler, Storz, & Wittchen, 2000 ). Sexually abused boys are at higher risk of later becoming sexual abusers themselves (Aebi et al, 2015 ), and those who have witnessed violence against their mothers are more likely to become perpetrators of intimate partner violence (Hotaling & Sugarman, 1986 ) and community violence (Jewkes & Abrahams, 2002 ; Shields, Nadasen, & Pierce, 2009 ). The transformation from victim to perpetrator is an adaptation that entails advantages for those who have begun to feel attracted to cruelty.…”
mentioning
confidence: 99%
“…PTSD rates in adolescents from the low-income areas of South Africa have been found to be between 20 and 25% (Seedat, Nyamai, Njenga, Vythilingum, & Stein, 2004 ; Suliman et al, 2009 ), which is at least three times the rates of European and North American adolescents (Kessler, Sonnega, Bromet, Hughes, & Nelson, 2005; Perkonigg, Kessler, Storz, & Wittchen, 2000 ). Sexually abused boys are at higher risk of later becoming sexual abusers themselves (Aebi et al, 2015 ), and those who have witnessed violence against their mothers are more likely to become perpetrators of intimate partner violence (Hotaling & Sugarman, 1986 ) and community violence (Jewkes & Abrahams, 2002 ; Shields, Nadasen, & Pierce, 2009 ). The transformation from victim to perpetrator is an adaptation that entails advantages for those who have begun to feel attracted to cruelty.…”
mentioning
confidence: 99%
“…In Support of path b in Figure 1, and as reported in Table 1, studies have further found positive associations between exposure to violence in Africa with children's health problems in terms of PTSD symptoms, internalizing problems including symptoms of depression and anxiety, psychological distress, as well as externalizing problems including antisocial behaviors, aggressive behaviors, conduct problems and substance use (Bach & Louw, 2010; Betancourt, Borisova et al, 2010; Betancourt, Brennan et al, 2010; du Plessis, Kaminer, Hardy, & Benjamin, 2015; Fincham et al, 2009; Kaminer et al, 2013; Martin et al 2013; Shields 2009a, 2009b; Waller, Gardner, & Cluver, 2014). …”
Section: Methodsmentioning
confidence: 86%
“…School, family, and peer social support were found to decrease the effects of gang violence on psychological distress, while the positive association between hearing about violence and psychological distress was mitigated by higher levels of family organization (Shields et al, 2008). Finally, individual resources also showed a trend toward significance in modifying the effects of violence exposure, where children with a low unknown locus of control (i.e., not knowing why events happened) had lower distress than those with a higher unknown locus of control (Sheilds et al, 2009b). Gender also modified some of the effects of violence exposure on children's health (Betancourt, Borisova, de la Soudiere, & Williamson, 2011; Betancourt, McBain, Newnham, & Brennan, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations